2016
DOI: 10.1007/s11030-015-9654-7
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and biological assays of novel 2,4-disubstituted hydrazinyl-thiazoles analogs

Abstract: A convenient, one-pot multi-component synthesis of new 2,4-disubstituted hydrazinyl-thiazoles was accomplished using different aldehydes/ketones, thiosemicarbazide, and 4-methoxy phenacyl bromide in the presence of a catalytic amount of AcOH in EtOH. Products were obtained in reasonable yields and high purity. The in vitro antioxidant activity of hydrazinyl-thiazoles was evaluated by DPPH radical scavenging activity in comparison to ascorbic acid. Synthesized thiazoles 14c and 14g possessed the lowest IC50 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, these compounds showed better antibacterial activity against P. aeruginosa and S. aureus than our products because of the presence of the coumarinyl moiety. Moreover, in our recent study, 2,4‐disubstituted hydrazinyl‐thiazoles showed antibacterial activity against S. aureus , M. luteus , E. coli , P. aeruginosa , B. subtilis , and A. hydrophila with the zones of inhibition of 6–11, 7–10, 9–13, 7–17, 6–21, and 6–11 mm, respectively, and these products showed antibacterial activity against E. coli .…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…However, these compounds showed better antibacterial activity against P. aeruginosa and S. aureus than our products because of the presence of the coumarinyl moiety. Moreover, in our recent study, 2,4‐disubstituted hydrazinyl‐thiazoles showed antibacterial activity against S. aureus , M. luteus , E. coli , P. aeruginosa , B. subtilis , and A. hydrophila with the zones of inhibition of 6–11, 7–10, 9–13, 7–17, 6–21, and 6–11 mm, respectively, and these products showed antibacterial activity against E. coli .…”
Section: Resultsmentioning
confidence: 78%
“…Some proposed radical structures and resonance of radical through the structure of bis‐thiazole 6i are depicted in Scheme . Ultimately, compounds 6a–l, especially 6i–j, can be introduced as potent antioxidant compounds similar to our recently synthesized hydrazinylthiazoles …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This functional group is present in prothinoamide antimycobacterial drug (Bartels and Bartels, 1998). Thiazole ring itself is a biologically active component and recently synthesised 2, 4-disubstituted hydrazinyl-thiazoles have been introduced as antibacterial, antioxidant and anticancer agents (Ghanbari Pirbasti and Mahmoodi, 2016). The best result in antibiogram test was observed with penicillin antibiotic against S. İniae with MIC value of 0.5 µg ml -1 .…”
mentioning
confidence: 99%